EFFECT OF AFRICAN LEAF EXTRACT (Vernonia amygdalina) ON ALLOXANINDUCED DIABETES MELLITUS LEYDIG CELL MYTOSIS OF WISTAR RATS - Tanaem, C Angela; Rosalind, L Aurellia (JOURNAL OF WIDYA MEDIKA JUNIOR, 2021)
Introduction: Diabetes mellitus can reduce the quality of human life when accompanied bycomplications, one of which is sexual dysfunction. In diabetics, there is an increase in ROSproduction which can cause damage to local Leydig cell proliferation so that Leydig cellactivity and testosterone secretion decrease. African leaves can be used as a control of bloodsugar levels and antioxidants to overcome oxidative stress. Purpose: To determine the effect of administration of African leaf extract (Vernoniaamygdalina) on alloxan-induced Leydig cell mitosis in male rats with diabetes mellitus.Method: This experimental study used 31 male Rattus norvegicus white rats divided into K,P0, P1, P2, and P3 groups. Each group consisting of six rats and one rat outside the study group was used as a reference. Experimental animals will be induced alloxan with a single dose of 150 mg/kgBW for four days. African leaf extract was administered using a probe togroups P1, P2, P3 at a dose of 100, 200, and 400 mg/kgBW for 14 days. Rats wereanaesthetized and euthanized so that the testes could be used to make preparations with HEstaining and analysis of preparations using a 400x magnification light microscope. Theresearch data were analyzed using One-Way Annova with P<0.05. Results: The administration of African leaf extract affected increasing the number of mitoticLeydig cells (P=0.026). There was a significant increase in the number of mitotic Leydig cellsat a dose of 100 mg/kgBW (P=0.021), but not effective at a dose of 200 mg/kgBW (P=0.188)and 400 mg/kgBW (P=0.823). Conclusion: The administration of African leaf extract at a dose of 100 mg/kgBW has beenshown to increase the number of mitotic Leydig cells so that it can be used to improve sexualfunction in diabetics.